Geographic distribution of the genus Pleurodema in Argentina (Anura: Leiuperidae) - Ferraro, Daiana P.; Casagranda, M. Dolores (Zootaxa, 2009)
Distributional ranges of South American frogs are usually poorly known. In this paper, we examined 4671 specimens of the genus Pleurodema deposited in Argentinean herpetological collections and used these museum data to generate distributional maps for the nine species of the genus currently known in Argentina (P. cf. borellii, P. bufoninum, P. cf. cinereum, P. kriegi, P. guayapae, P. marmoratum, P. nebulosum, P. thaul and P. tucumanum). Then, we contrasted the distributional ranges of each species with ecological regions proposed for the country. The species of the genus Pleurodema are widely distributed along northwestern, central, western, and southern Argentina from sea level up to 4275 m a.s.l., and all of them occur at protected areas of the country. We listed localities where two or more species live in sympatry. We found a correlation between point-occurrence data and distance to main roads of the country, where 50% of specimens were collected at a distance minor than 2 km from main roads. Finally, we discussed doubtful records of Pleurodema species taken from both museum records and literature on the basis of our knowledge about the distributional range of these species.